PENGARUH APLIKASI PUPUK SULFUR DAN JUMLAH SIUNG TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG PUTIH (Allium sativum L.) SERTA RESIDU SULFUR DI INCEPTISOL KARANGPLOSO - Balqis Noor Hanifah; Retno Suntari; B Baswarsiati (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Garlic (Allium sativum L.) is a plant that is often used by Indonesian people in various ways. One of the reasons for the low productivity of garlic in Indonesia is the insufficient use of superior varieties and low S elements in the soil. Furthermore, the use of the number of cloves planted per planting hole will determine the number of populations so that it will affect the growth and production of garlic. The aim of this study was to analyze the effect of S fertilizer and the number of cloves on the growth and production of garlic (Allium sativum L.) and also analysis S residue from S fertilizer and number of cloves. This study used a randomized block design with nine treatment combinations, three levels of sulfur fertilizer doses (0 kg S ha-1, 140 kg S ha-1 and 200 kg S ha-1) and the number of cloves (1 clove, 2 cloves and 3 cloves). The results showed that the application of sulfur fertilizer and the number of cloves had no significant effect on growth parameters (plant height and number of leaves) in garlic plants. However, it significantly increased the diameter of bulbs, fresh bulbs weight and dry bulbs weight respectively by 13.39%, 140.72% and 93.64% to 24.29 mm, 5.97 g plant-1 and 4.57 g plant-1 in the treatment of one number of clove and 140 kg of S ha-1 compared to the treatment of one clove and without S. As well as significant effect on SO42- residues and total S with the highest yield respectivelyÂ  299.3 ppm and 910 ppm and the lowest yield was obtained in the treatment without S fertilizer.